SOCIALIZATION OF PETATAH-PETITIH IN THE COMMUNITY IN THE WATER VILLAGE SANTOK SUB-DISTRICT OF EAST PARIAMAN CITY OF PARIAMAN - Alfajri Yusra; Firman Firman; Rusdinal Rusdinal (Kurikulum Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2019)
In the current problem, the Minangkabau language user, especially in the village of Air Santok, East Pariaman Subdistrict, Pariaman City no longer understands the lack of understanding of the meaning of Petatah-Petitih. For this reason, it is necessary to socialize it so that the people of the village of Air Santok, especially for the next generation, can understand the values in the Petatah-Petitih Minangkabau. This research was conducted in the village of Air Santok, Pariaman Timur District, Pariaman City. This type of research uses a qualitative approach to the form of case study research, the informants selected using the purposive sampling technique. The results of the research carried out are that 1) What is socialized in Petatah-Petitih, instill values such as proverbs which contain advice and teachings of parents conveyed in the form of rhymes 2) How to socialize the Petatah-Petitih, at this time carried out by the village government Air Santok, with village programs that provide training to the community. 3) Who socializes Petatah-Petitih namely Kapalo Mudo as a teacher appointed by the village government.